Effect of MRJF4 on C6 Glioma Cells Proliferation and Migration - Pacella, Stephanie; Fiorito, Jole; Cacciatore, Ivana; di Giacomo, Viviana; Patruno, Antonia; Rapino, Monica; Di Stefano, Antonio; Marinelli, Lisa; Fornasari, Erika; Cataldi, Amelia; Prezzavento, Orazio; Marrazzo, Agostino (Central Nervous System Agents in Medicinal Chemistry, 2017)
Background: MRJF4, a novel haloperidol metabolite II prodrug, was obtained through the esterification of the secondary hydroxyl group of haloperidol metabolite II with 4-phenylbutyric acid. The activities of (±)-MRJF4 and its two enantiomers [(+)-MRJF4 and (-)-MRJF4] as tumor specific inducers of pro-apoptotic genes were evaluated on malignant C6 glioma cells. In particular, changes in Nf-ΚB signaling pathway, activity of nitric oxide synthases (NOS), metalloproteinases (MMPs), and membrane adhesion proteins were investigated. Results: IΚBα reduced phosphorylation and iNOS lowered activity could be correlated with the previously demonstrated decreased proliferation and tumor progression of C6 cells upon 24 h of treatment with all the three compounds. Integrin β1 decreased expression, at the same experimental time, seems to support lower C6 cells migrative capability and the consequent reduced invasiveness of these cells upon treatment with (±)-MRJF4 and its enantiomers. Conclusion: These results suggest that this multi-target prodrug and its two enantiomers might be a valuable clinical tool for the treatment of metastatic glioblastoma.
Keywords: MRJF4